Continuous carbon fiber reinforced composite negative stiffness mechanical metamaterial for recoverable energy absorption. (15th May 2022) - Chen, Shuai; Tan, Xiaojun; Hu, Jiqiang; Wang, Bing; Wang, Lianchao; Zou, Yajun; Wu, Linzhi
Abstract: This study investigated negative stiffness (NS) mechanical metamaterials, which are potential in the energy absorption field. However, critical drawback of low specific energy absorption in traditional NS mechanical metamaterials limits them to be applied. In this paper, a reusable continuous carbon fiber reinforced polymer (CFRP) composite NS mechanical metamaterial was proposed and fabricated. A combination of compression tests and numerical simulations have been carried out to gain a comprehensive understanding of the structural quasi-static mechanical properties. Repeatability of the metamaterial was then verified by cyclic compression. The results of quasi-static test show that the metamaterial has excellent reusability characteristics and good energy absorption capability. In addition, the effect of the structural parameters on the mechanical properties was revealed using the experimentally verified numerical model. Moreover, by dint of the numerical model, the effect of stacking sequence of the metamaterial on the mechanical properties was also investigated, and the correctness of the curved beams adopted 0° stacking sequence in this paper was proved. Finally, plate-impact tests were performed to investigate the cushion performance of this metamaterial. The metamaterial structure shows good impact resistance without the occurrence of any plastic deformation. The research has guiding significance for the design of impact-resistant metamaterials.